Anterior Segment Optical Coherence Tomography-guided Diagnosis and Management of Late Graft Dehiscence Post Tuck-in Lamellar Keratoplasty - Ritu Arora; Shipra Sharda; Parul Jain; Avani Hariani; Isha Gupta (Delhi Journal of Ophthalmology)
The purpose of the study was to describe the management of graft host separation in an operated case of tuck-in lamellar keratoplasty (TILK) for pellucid marginal degeneration in a young male guided by anterior segment optical coherence tomography (AS-OCT). TILK as a procedure has several advantages over full-thickness penetrating keratoplasty. In this case, a TILK was performed, which underwent undesired wound dehiscence a few weeks postsuture removal, which was managed successfully with the help of AS-OCT-guided suturing and gas tamponade. Suture removal post-TILK should be done with utmost care and precision after 6 months postsurgery, preferably guided by ASOCT after assessing the graft host apposition.